Extinction rates under nonrandom patterns of habitat loss - Seabloom, E. W.; Dobson, A. P.; Stoms, D. M. (Proceedings of the National Academy of Science of the United States of America, 2002)
Most models that examine the effects of habitat conversion on species extinctions assume that habitat conversion occurs at random. This assumption allows predictions about extinction rates based on the speciesarea relationship. We show that the spatially aggregated nature of habitat conversion introduces a significant bias that may lead species-loss rates to exceed those predicted by speciesarea curves. Correlations between human activity and major compositional gradients, or species richness, also alter predicted species extinction rates. We illustrate the consequences of nonrandom patterns of habitat conversion by using a data set that combines the distribution of native vascular plants with human activity patterns in California.